If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3(2x+1)=12+x
We move all terms to the left:
3(2x+1)-(12+x)=0
We add all the numbers together, and all the variables
3(2x+1)-(x+12)=0
We multiply parentheses
6x-(x+12)+3=0
We get rid of parentheses
6x-x-12+3=0
We add all the numbers together, and all the variables
5x-9=0
We move all terms containing x to the left, all other terms to the right
5x=9
x=9/5
x=1+4/5
| -12x-6=-60 | | 11+8y=11 | | 6-5t=16 | | 1-3b+7=9-4b | | 65-s=15 | | 10−2r=–4 | | 6(u+8)=-4u+38 | | 3v−3=12 | | 15=9^x+2 | | -12x+18=-60 | | 65-s= | | 5x2–2=18 | | x=11/2=6 | | 47+7x+15=180 | | 9(x+6)=-207. | | 2−3j=–1 | | -5x2=3-4 | | 47=7x+15 | | -9(x+6)=-207. | | 39=14+8x | | 2/7p-2=p+3 | | 3(-5y+4)=-8y-2+3y-6 | | 2u−15=5 | | 21.4+126+x=180 | | 0=-0.03x^2+1.3x+16 | | 9.84+5m=1.8m-10 | | f+10=-2f-10-10 | | -3-33=6(w+5) | | 58+70+x+63=180 | | 3(x-12.5)=-3.41 | | 2x+0.3=8.1 | | -0.52x+0.22x=8.7 |